Éloge et critique de l’efficience économique : Quesnay, Smith, Rousseau - Claire Pignol (Etudes Epistémè)
Economic efficiency is defined in the 18th century, by Quesnay as well as by Smith, as the maximization of the surplus generated by an economy. For Quesnay, the surplus is consumed for pleasure, while for Smith it is mainly accumulated in order to increase the productive power of labor. Rousseau is constantly hostile to efficiency, wants to proscribe any invention that might shorten labor, and urges the production of only perishable goods. Rousseau, although he praises the superfluous, also points out the threats that its uses and its consequences bring to the agents’ expectations, when it turns into a necessity whose deprivation is painful. Where Smith encouraged a far-sighted agent to save for his future happiness, Rousseau invites a foresight that accepts the transience of pleasures and is able not to depend on the permanence of present wealth.